A plethora of Type IIA embeddings for d = 5 minimal supergravity - Couzens, C; Macpherson, NT; Passias, A (Springer, 2023)
We construct multiple embeddings of all solutions of d = 5 minimal (un)gauged supergravity into massive Type IIA supergravity. The internal spaces and warpings of such embeddings are the same as those of the N = 1 supersymmetric (Mink5) AdS5 vacua, with the slight modification that the U(1) R-symmetry direction becomes fibered over the external space by the d = 5 gauge field. In addition the fluxes are appropriately modified. There are many distinct types of the aforementioned internal spaces and as such many different embeddings of the d = 5 supergravity. As examples of our setup we provide new solutions dual to six-dimensional, N = (1, 0) SCFTs compactified on the product of a constant curvature Riemann surface and a spindle. We also provide a multitude of massive Type IIA embeddings for rotating, asymptotically AdS5 black hole solutions.